A critical analysis of higher-order beliefs in Richard Moran’s conception of transparency relations - Tong, Chermaine (Nanyang Technological University, 2020)
In the following thesis, I will aim to explicate Richard Moran and his influences’ accounts of transparency as a property in Self-Knowledge, primarily in reference to his book; Authority and Estrangement: An Essay on Self-Knowledge. I seek to critically analyse the transparency dialectic’s lapse in a strict definition of how a higher-order belief is constituted, and how it will affect Moran’s interpretations of transparency and applications to a realistic working system of belief formation. This paper intends to at the forefront, evaluate the problems self-knowledge has with asserting transparency as a property, and subsequently, focus on shedding light on this disparity of higher-order belief definitions clearly within Moran’s perimeters. Therefore, establishing a push for the dialectic to tackle its core definitions via an extensive critique of the various concerns the transparency account must face in order to counter any objections against self-knowledge beliefs and avowals being transparent.